Copper(I) Iodide-Catalyzed (Het)arylation of Diethyl Malonate with (Het)aryl Bromides by Using 1,3-Benzoxazole as a Ligand - Zeng, Yu; Zheng, Hao-liang; Yang, Zhao; Liu, Cheng-Kou; Fang, Zheng; Guo, Kai (Synlett, 2018)
An efficient Ullmann-type coupling of aryl bromides with diethyl malonate in the presence of copper(I) iodide and 1,3-benzoxazole is presented. This method has a broad substrate scope (heterocyclic and phenyl bromides) and good functional-group tolerance (OMe, Me, Ac, CN, NO2, F, and Cl). Moreover, less time is needed to reach full conversion (3–9 hours).
Keywords: Ullmann coupling; benzoxazole; copper catalysis; aryl bromides; hetarylation; arylation